Effect of shade and level of fertilizer application on nutrient uptake and dry matter partitioning in cocoyam (Xanthosoma sagittifolium L.) - Asante, M.O.O.; Ahiakpa, J.K.; Amoatey, C.; Adjei-Nsiah, Samuel (Informa UK Limited, 2017)
The effect of shade and fertilizer application on nutrient uptake and dry matter (DM) partitioning in cocoyam was evaluated by growing the plant under different levels of shade and fertilizer application at Forest and Horticultural Crops Research Centre, Kade, within a period of 9 months. The shade levels used were 80%, 70%, and 50% shade, and full sunlight exposure. The fertilizer rates used were 112 kg/ha nitrogen, phosphorus and potassium (NPK) (15-15-15 120 kg/ha NPK (15-15-15) in a form) of mineral fertilizer, 112 kg/ha NPK organic fertilizer and no fertilizer (control). The split-plot design was used with shade levels as the main plot factor and fertilizer levels as the sub plot factor. The interaction effect of shade and fertilizer had a significant effect (p ≤ 0.05) on DM of cocoyam leaves, petioles, corm, and cormels as well as nutrient accumulation in plant parts. Cocoyam leaves of plants grown under 50–70% shade stored significantly higher (p ≤ 0.05) quantities of nutrients (1.51 ppm of N, 6.61 ppm of P, and 53.10 ppm of K) and accumulated more DM (71.30 g) than leaves of plants grown under full sunlight exposure which accumulated 1.37 ppm of N, 4.31 ppm of P, 26.06 ppm of K, and 30.7 g DM, at the two rates of the chemical fertilizer application. Under full sunlight exposure, significantly higher amounts of DM were accumulated in the corms and cormels at mineral fertilizer level of 112 kg/ha. At mineral fertilizer rate of 120 kg/ha, nutrient accumulation was significantly higher (p ≤ 0.05) in the corm and cormels (1.72 ppm of N and 7.72 ppm of P) of plants grown under full sunlight exposure than those grown under 70% shade level (0.6 ppm of N and 2.94 ppm of P). Nitrogen and phosphorus accumulation was significant in the petioles of plants grown under the 70% shade level at fertilizer rate of 120 kg/ha. It is recommended that cocoyam be grown under 50–70% shade at a fertilizer rate of 112–120 kg/ha for leaf production and under full sunlight exposure at 112 kg/ha (NPK) for cormel production.